Palliation of malignant dysphagia with a segmented self-expanding metal stent: A STROBE-compliant article. Issue 34 (27th August 2021) - Wiese, Marie-Sophie; Dratsch, Thomas; Plum, Patrick Sven; Lorenz, Florian; Rieck, Isabel; Pinto dos Santos, Daniel; Alakus, Hakan; Bludau, Marc; Kleinert, Robert; Goeser, Tobias; Bruns, Christiane Josephine; Chon, Seung-Hun
Abstract : Abstract: Self-expanding metal stents (SEMSs) in different geometric shapes are an established palliative treatment for malignant tumors of the esophagus. Mechanical properties and stent design have an impact on patient comfort, migration rate, and removability. SEMS with a segmented design (segSEMS) have recently become available on the market, promising new biomechanical properties for stent placement in benign and malignant esophageal diseases. In this study, we evaluated recurrent dysphagia, quality of life as well as technical success and complications for segmented SEMS-implantation in a retrospective study in palliative patients with dysphagia caused by malignant tumors of the esophagus. Between May 2017 and December 2018, patients presented to the interdisciplinary department of endoscopy of the University Hospital Cologne underwent segmented SEMS placement for malignant dysphagia. Patient follow-up was evaluated, and complications were monitored. Quality of life and functional improvement were monitored using the EORTC QLQ-C30 and QLQ-OE18. A total of 20 consecutive patients (16 men, 4 women; mean age: 65.5, range: 46–82) participated in the study and were treated with 20 segSEMS in total. The success rate of stent placement was 100%. Stent migration occurred in 3 patients (15.0%). Insertion of segSEMS immediately lead to a 48.0% reduction of dysphagia in the first 2 months ( P < .001). Pain while eating (odynophagia) could also be significantly reduced by 39.6% over the first 2 months ( P < .001). Implantation of segSEMS is a feasible and effective treatment for dysphagia in palliative patients with malignant tumors of the esophagus, offering immediate relief of symptoms and gain of physical functions.